Restrictive Practices in Adult Secure Mental Health Services: A Scoping Review. Issue 1 (2nd January 2022) - Lawrence, Daniel; Bagshaw, Ruth; Stubbings, Daniel; Watt, Andrew
Abstract: Restrictive practices are often harmful and many academics, policy-makers and clinicians agree that their use should be reduced in care settings. Specific focus on secure mental health services is warranted because restrictive practices are often seen as an integral part of forensic psychiatry but have received limited research attention relative to other areas of psychiatric practice. The aim of this scoping review was to map and evaluate recent empirical research that examines the use of restrictive practices, the consequences of using them and efforts to reduce restrictive practices, in secure mental health settings published since June 2015. The purpose of this review was to identify limitations and gaps in the literature in order to inform further research. PsycINFO, Medline, Embase, CINAHL, Scopus and ASSIA databases were searched for studies published between 2015 and 2020. Following electronic and manual searches, 36 studies were included. The studies were grouped into four main areas: 1) Nature of the problem describing the type, incidence, prevalence and scope of restrictive practices in secure mental health services; 2) Service user perceptions and experiences of restrictive practices; 3) Staff experiences, views and decision making; and 4) Interventions designed to reduce the use of restrictive practices. Findings support the notion that restrictive practices have a detrimental impact on the wellbeing of most service users in adult secure services as well as the staff who use them. Continued efforts to reduce restrictive practices are needed and the importance of collaborative working cannot be understated. Implications for future research, clinical practice, policy and best practice guidelines are all discussed.